People's Republic of China : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the People's Republic of China. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights China's continuing transition to a more sustainable growth path and the advance of reforms across a wide domain. Growth slowed to 6.7 percent in 2016 and is projected to remain robust, at 6.7 percent, in 2017 owing to the momentum from last year's policy support, strengthening external demand, and progress in domestic reforms. Inflation rose to 2 percent in 2016 and is expected to remain stable, at 2 percent, in 2017. Essential supervisory and regulatory action is being taken against financial sector risks, and corporate debt is growing more slowly, reflecting restructuring initiatives and overcapacity reduction.